2021
DOI: 10.3390/cells10051163
|View full text |Cite
|
Sign up to set email alerts
|

Anthracyclins Increase PUFAs: Potential Implications in ER Stress and Cell Death

Abstract: Metabolic and personalized interventions in cancer treatment require a better understanding of the relationship between the induction of cell death and metabolism. Consequently, we treated three primary liver cancer cell lines with two anthracyclins (doxorubicin and idarubin) and studied the changes in the lipidome. We found that both anthracyclins in the three cell lines increased the levels of polyunsaturated fatty acids (PUFAs) and alkylacylglycerophosphoethanolamines (etherPEs) with PUFAs. As PUFAs and alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 75 publications
3
13
0
Order By: Relevance
“…The lower IC 50 values at longer exposure times observed in this study could be attributed to an overall increased cellular uptake of DOX and a subsequent accumulation inside the cell nucleus, where it induces cell death through different mechanisms, including ferroptosis [ 45 , 46 ]. However, the effect of further exposure time is significantly decreased or ceases between the 48 to 72 h time interval for the HepG2, SNU449 and MCF7 cell lines, while it might be maintained for Huh-7 [ 29 , 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower IC 50 values at longer exposure times observed in this study could be attributed to an overall increased cellular uptake of DOX and a subsequent accumulation inside the cell nucleus, where it induces cell death through different mechanisms, including ferroptosis [ 45 , 46 ]. However, the effect of further exposure time is significantly decreased or ceases between the 48 to 72 h time interval for the HepG2, SNU449 and MCF7 cell lines, while it might be maintained for Huh-7 [ 29 , 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…During low levels of ER stress, activation of these pathways is correlated to increased translation of genes regulating ER chaperones, amino acid metabolism, redox reactions, autophagy, protein folding, and maturation, which is generally thought of as a pro-survival mechanism [ 8 , 9 , 10 , 11 ]. In comparison, high levels or prolonged ER stress have been shown to trigger apoptotic pathways via caspase-3, BCL-2 family member, apoptosome complex activation, and ferroptosis [ 17 , 18 , 19 ]. How and when different ER stress pathways exert their cytoprotective or their pro-apoptotic functions remains largely unknown.…”
Section: Endoplasmic Reticulum Stress In Health and Diseasementioning
confidence: 99%
“…Expression of prognostic ER stress proteins such as GADD34, eIF2α, CHOP, and ATF4, being regulated by PERK, were shown to be involved in apoptosis, as well as in chemo-responsiveness [ 37 , 83 ]. Meanwhile regarding ferroptosis, another type of cell death [ 84 ], recent studies have shown there is a cross-talk between ER stress and the lipidome that mediates chemoresistance when responding to anthracyclines, such as doxorubicin and idarubicin [ 18 ]. The lipid membrane composition was established to be the main factor affecting drug fluidity and membrane permeability.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…For instance, it has been demonstrated that both idarubicin and doxorubicin increase the levels of polyunsaturated fatty acids (PUFAs) and alkylacylglycerophosphoethanolamines (etherPEs) in different HCC-cell lines with markedly different drug-responses [ 125 ]. The fact that these lipids are fundamental in lipid peroxidation during ferroptotic cell death suggests that supplementation of these lipids may have the potential to act as a general adjuvant of idarubicin and doxorubicin in TACE treatment.…”
Section: The Future Of Tacementioning
confidence: 99%
“…Modulating the different lipid metabolic pathways could also form a new treatment strategy and contribute to generalized and personalized metabo-chemotherapies. In addition, it has been demonstrated that doxorubicin in itself induces the unfolded protein response pathways in different tumour cell lines [ 125 ]. Activation of unfolded protein response is known to induce drug resistance in HCC [ 126 , 127 ].…”
Section: The Future Of Tacementioning
confidence: 99%